2005
DOI: 10.1007/s00168-004-0213-x
|View full text |Cite
|
Sign up to set email alerts
|

From physical to general spaces: A spatial econometric analysis of cross-country economic growth and institutions

Abstract: C21, O18, O53, R11, R58,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…For instance, economic growth in a region or country can be influenced by regional business cycles, flows of trade, capital, and migration, as well as political instability and armed conflicts, technology diffusion, access to product and input markets, and common economic, political, and social arrangements (Moreno and Trehan 1997, Ades and Chua 1997, Ramirez and Loboguerrero 2002, Ying 2005. From a more practical perspective, Rey and Montouri (1999) also discuss the possibility that boundary mismatch problems can produce spatial correlation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, economic growth in a region or country can be influenced by regional business cycles, flows of trade, capital, and migration, as well as political instability and armed conflicts, technology diffusion, access to product and input markets, and common economic, political, and social arrangements (Moreno and Trehan 1997, Ades and Chua 1997, Ramirez and Loboguerrero 2002, Ying 2005. From a more practical perspective, Rey and Montouri (1999) also discuss the possibility that boundary mismatch problems can produce spatial correlation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that the links between markets have become even closer as COVID-19 has spread around the world than those of any other risk. The same applies to the work of Guidolin and Pedio, 2017 , Guo et al, 2011 , Haidar, 2012 , Haile and Pozo, 2008 , Hansen, 2021 , Wu et al, 2011 , Ying, 2005 who proved that the intense links between financial markets and also the degree of financialization and opening of the capital account are factors that amplify the relationships between financial markets and can facilitate the occurrence of contagion shocks.…”
Section: Literature Reviewmentioning
confidence: 73%
“…(2) Research on the impact of green innovation capability on regional economic development In terms of the impact on regional economic development, Cheng Li (2016) concluded that the current development status of Tianjin is relatively good, and the overall development is toward a high-level level through the spatial evaluation method of the coordinated development of regional environmental economy [7]. Zhang Zhiying et al (2019) took 30 provinces in China as research objects, built a green innovation indicator system, and used a spatial econometric model to study the relationship between green innovation and regional economic growth [8]. Chen Guoqing et al (2020) established an evaluation system of green innovation and economic development, and used the data of Sichuan Province from 2007 to 2018, such as the gross regional economic product, R&D expenditure and scientific and technological innovation investment, to establish a grey correlation analysis model and study the relationship between the two [9].…”
Section: Literature Reviewmentioning
confidence: 99%